Infecções relacionadas à assistência à saúde em unidades de terapia intensiva de adultos no Brasil: Estudo multicêntrico da prevalência, fatores de risco e consumo de antimicrobianos - Machado, Luiz Gustavo (2022)
Introduction: Health care-associated infections (HCAIs) are a collective problem with a great impact on patient mortality and morbidity, especially in countries with few resources such as Brazil. Objectives: This study aimed to map, through a multicenter study, the prevalence of HCAIs caused by epidemiologically important pathogens, as well as to assess risk factors and antimicrobial consumption in adult intensive care units (ICU) in Brazil. Additionally, the frequency of carbapenems resistance genes in Acinetobacter baumannii and Klebsiella spp. Methods: Since 2016, we have been conducting multicenter point prevalence surveys in adult ICUs in Brazil. So far, we have included 39 institutions totaling 45 clinical-surgical ICUs and 7 coronary ICUs. Hospitals were stratified according to type and size. Additionally, a paired case-control study was conducted to determine the risk factors associated with HCAIs. The blaOXA-51, blaOXA-23, blaOXA-24, blaOXA-58 and blaOXA-143 genes in A. baumannii and blaKPC and blaNDM-1 genes in Klebsiella spp. were detected by PCR in the samples retrieved from the different hospitals included in the study. Results: A total of 664 patients admitted to Adult ICUs were included, of which 550 were patients in clinical-surgical units (CCU), of which 214 (38.9%) were infected and 190 patients had at least one ICU-acquired infection (88.8%). %). The most frequently acquired infections in these units were pneumonia (54.1%) and bloodstream infection (32.8%). In its totality, 177 bacterial samples were observed as the cause of HCAIs, with a higher frequency of Gram-negative bacilli (34.6%). In adult coronary ICUs, 114 patients were evaluated and the prevalence of HCAIs was 25.4% and those acquired in the ICU was 82.7%. The most frequent infections in these units were also pneumonia (56.0%), followed by bloodstream infection (28.0%). Only 34.5% of infected patients had been treated based on microbiological criteria. Neoplasm was an independent factor in the risk of infection, However, invasive procedures usage and their concomitant use also proved to be an important factor. Amid the number of patients, 444 (66.9%) received at least one antimicrobial, and 54.4% received empirical treatment. The results also detected a high consumption of broad-spectrum antibiotics, mainly carbapenems, in most regions. As for polymyxins, 5.3% of the patients were using them. All A. baumannii samples showed the blaOXA-23 gene and 33.3% of the Klebsiella spp. had the presence of the two genes blaKPC and blaNDM-1. Conclusions: This multicenter study provides alarming data on HCAIs and antimicrobial consumption in Brazil, presenting high rates of those with the worst prognosis such as pneumonia and bloodstream infections caused mainly due to Gram-negative bacilli (GNB). Just as important, it was the high empirical prescription frequency of antimicrobials.